Вплив похибок планового характеру на точність визначення об’ємів ґрунту - Гарасимчук, І. Ф.; Тревого, І. С.; Власенко, С. Г.; Муха, В. І. (Видавництво Національного університету «Львівська політехніка», 2001)
Рассмотрен вопрос влияния погрешностей планового характера на точность определения объемов грунта. Установлено, что плановые погрешности, особенно систематические, могут значительно влиять на точность определения объемов. Указаны пути уменьшения их влияния. ТЬе problem of influence of the plane errors on the accuracy of the determination of the volume of soil was considered. It was established that plane errors (especially systematical) may considerably influence on the accuracy of the determination of the volumes. The ways of their decrease were indicated.